Patient Characteristics Associated with Seizure Freedom after Vagus Nerve Stimulation in Pediatric Intractable Epilepsy: An Analysis of “Super-Responders” - Tamura, Goichiro; Lo, William B.; Yau, Ivanna; Vaughan, Kerry A.; Go, Cristina; Singleton, William G.B.; Hazon, David; Yan, Han; Otsubo, Hiroshi; Donner, Elizabeth J.; Rutka, James T.; Ibrahim, George M. (Journal of Pediatric Epilepsy, 2021)
Clinical responses to vagus nerve stimulation (VNS) therapy for intractable epilepsy can be unpredictable, and factors that predict response to therapy are elusive. Minority of children undergoing VNS achieve seizure freedom. The current study aimed to characterize this exceptional patient population, defined as “super-responders” (SRs). Retrospective data were collected from 150 children who underwent VNS at a single pediatric institution. The patients' mean age at VNS device implantation was 12.0 years (range, 3.09–17.9 years). Ten SRs (6.7%) were identified who achieved and maintained seizure freedom for longer than 1 year following implantation. The interval between epilepsy onset and VNS device implantation was significantly shorter in SRs than in the other children (mean epilepsy duration 5.72 vs. 8.44 years, respectively; p = 0.032). SRs also had a significantly shorter proportion of life with epilepsy compared with the other children (mean ratio of epilepsy duration to age at implantation 0.52 vs. 0.71, respectively; p = 0.023). SRs reported their seizure freedom relatively early (six patients within 6 months and all patients within 12 months after implantation) at relatively low device settings (mean output current 0.81 mA at their last follow-up). Compared with conventional models, responsive VNS models with autostimulation features did not increase the ratio of SRs. No other clinical or imaging characteristic difference between SRs and the other children was found in this cohort. The current study showed a significant association between shorter epilepsy duration and shorter proportion of life with epilepsy and seizure freedom after VNS.
Keywords: vagus nerve stimulation; seizure freedom; pediatric; epilepsy; predictor